2022
DOI: 10.20944/preprints202212.0533.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Actual Bibliometric/Scientometric Issues Based on 2018-2022 Data from the Lens Platform by Building Key Term Co-occurrence Network

Abstract: The purpose of this article is to demonstrate the ability of bibliometric data from the Lens platform to identify relevant bibliometric/scientometric issues based on the construction of a network of key terms co-occurrence and their clustering. The advantages of using the Lens platform for bibliometric analysis are briefly demonstrated. Key terms were selected on the basis of n-grams and noun phrases. VOSviewer, Scimago Graphica, and Sifaka text mining application were used as analytical tools. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…17 Interestingly, in our search example, Lens yielded a lower number of articles compared to Scopus and WOS, despite being considered a more comprehensive and coverage database in comparison. 18 Regarding the distribution of authors between databases, a significant difference was observed in the number of documents in WOS compared to other databases. Additionally, WOS did not share any author within the top ten listed authors with authors from other databases.…”
Section: Discussionmentioning
confidence: 97%
“…17 Interestingly, in our search example, Lens yielded a lower number of articles compared to Scopus and WOS, despite being considered a more comprehensive and coverage database in comparison. 18 Regarding the distribution of authors between databases, a significant difference was observed in the number of documents in WOS compared to other databases. Additionally, WOS did not share any author within the top ten listed authors with authors from other databases.…”
Section: Discussionmentioning
confidence: 97%